Factors associated with short- and medium-term mortality after hospitalization for COPD exacerbation - Cano, Arantza; Esteban, Cristóbal; Larrea, Nere; Iriberri, Milagros; Sánchez, Raquel; Jiménez-Puente, Alberto; de-Miguel-Díez, Javier; Orive, Miren; Quintana, Jose María; Esteban, Cristóbal; Aramburu, Amaia; Aburto, Myriam; et al. (Respiratory medicine, 2025)
Hospitalization due to exacerbation is a critical event for patients with chronic obstructive pulmonary disease (COPD). This study aimed to identify predictive factors for mortality in patients post-hospitalization for COPD exacerbation and to determine differences in these predictors in the short and medium term. A prospective observational study involving 1635 patients hospitalized for COPD exacerbation, followed for one year. Sociodemographic and clinical data, comorbidities, treatments, and quality of life questionnaires were assessed. Cox regression analysis identified mortality predictors at 2 months and >2–12 months post-hospitalization. Mean age was 72.4 years with 76.6 % males. Overall, one-year mortality was 14.1 % (30.3 % of the deaths occurred within 2 months of discharge and 69.7 % occurred >2–12 months post-discharge). Short-term mortality predictors included: age (HR [95 % CI] = 2.483 [1.501–4.107]), lower Barthel index (HR [95 % CI] = 1.274 [1.063–1.526]), pulmonary function (FEV1 < 30 %: HR [95 % CI] = 5.153 [1.511–17.577]), and length of stay ≥8 days (HR [95 % CI] = 6.974 [2.504–19.419]). Medium-term predictors included: heart failure (HR [95 % CI] = 2.493 [1.318–4.717]), age (HR [95 % CI] = 1.690 [1.224–2.334]), lower Barthel index (HR [95 % CI] = 1.300 [1.149–1.472]), and pulmonary function (FEV1 < 30 %: HR [95 % CI] = 3.000 [1.351–6.658] and FEV1 30–50 %: HR [95 % CI] = 2.010 [1.046–3.862]). Mortality risk factors with exacerbated COPD after hospitalization vary over time. In the short term, length of hospital stay is prominent, while heart failure is more significant in the medium term. Age, dependency and pulmonary function were common predictors in both periods. Tailoring clinical interventions over time may improve health outcomes in this population. •Identifying predictors of short and medium term mortality in COPD is essential.•This large multicenter study provides some insights in that issue.•Short-term mortality predictors were length of hospital stay, age, dependency and pulmonary function.•Medium term mortality predictors were heart failure, age, dependency and pulmonary function.•Age, dependency and pulmonary function were common predictors to both mortality periods.